Transformation of Islamic Education Viewed From The Influence of Leadership Style, Managerial Cognitive Capability, and Job Satisfaction on The Organizational Commitment of Principals in Asahan District - Sagala, Suwastati; Mesiono, Mesiono; Ananda, Rusydi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to determine the transformation of Islamic education in terms of the influence of leadership style, managerial cognitive abilities, and job satisfaction on the organizational commitment of elementary school (SD) principals in Asahan Regency. This study focuses on transformation efforts in Islamic educational institutions. This research uses a quantitative approach, with a sample of 136 respondents through krejcie-based sampling. Test the validity of the instrument using the formula rcount > rtable. The results of this research conclude that there is an indirect influence of Leadership Style (X1) and management cognitive abilities (X2) through Job Satisfaction (X3) on the Organizational Commitment of School Principals in carrying out their duties (Y) in Asahan Regency amounting to 47.2% and 52.8 % is the simultaneous influence of Leadership Style and Management Cognitive Ability through Job Satisfaction on the Principal's Organizational Commitment.